2016
DOI: 10.1017/hpl.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Surface phase defects induced downstream laser intensity modulation in high-power laser facility

Abstract: Optics surface phase defects induced intensity modulation in high-power laser facility for inertial confinement fusion research is studied. Calculations and experiments reveal an exact mapping of the modulation patterns and the optics damage spot distributions from the surface phase defects. Origins are discussed during the processes of optics manufacturing and diagnostics, revealing potential improvements for future optics manufacturing techniques and diagnostic index, which is meaningful for fusion level las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To this end, herein we employ ultrafast transient absorption (TA) spectroscopy as it offers as traightforwarde xperimental means to track in real-time the charge-carrier dynamics (and hence the charge-transfer direction) in hybrid nanosystems. [3,36,37] Careful analysis of our TA results on the BiOCl(p)/g-C 3 N 4 (n) system (when compared to results measuring the individual components) demonstrates that the photogenerated electrons are transferred from the CB of BiOCl tot hat of g-C 3 N 4 ,n ot in the opposite direction. Moreover,s uch an electron-transfer process was found to occuro n at imescale of afew picoseconds.…”
mentioning
confidence: 88%
“…To this end, herein we employ ultrafast transient absorption (TA) spectroscopy as it offers as traightforwarde xperimental means to track in real-time the charge-carrier dynamics (and hence the charge-transfer direction) in hybrid nanosystems. [3,36,37] Careful analysis of our TA results on the BiOCl(p)/g-C 3 N 4 (n) system (when compared to results measuring the individual components) demonstrates that the photogenerated electrons are transferred from the CB of BiOCl tot hat of g-C 3 N 4 ,n ot in the opposite direction. Moreover,s uch an electron-transfer process was found to occuro n at imescale of afew picoseconds.…”
mentioning
confidence: 88%
“…Although the strategy and process for laser damage mitigation on KDP crystal surface have made great progress, the effect of KDP surface mitigation contours upon downstream far-field light modulation is unclear. The downstream light intensity modulation induced by the phase defects that lie on the reflection optics in one of the SG-III laser beamlines was studied by Zhang et al [17] . They found that these surface phased defects result in strong intensity modulation after some propagation distance.…”
Section: Introductionmentioning
confidence: 99%
“…The SCBHD was shown to be better than both. We furthermore proposed an improved setup to detect phase variation, by replacing the ordinary beam splitter (BS) with a polarization one, which is essential for large optics in high-power lasers and is related to the wavefront, damage threshold, and other parameters [16][17][18] .…”
mentioning
confidence: 99%